Metronomic and metronomic-like therapies in neuroendocrine tumors – Rationale and clinical perspectives. (April 2017) - Lambrescu, Ioana; Fica, Simona; Martins, Diana; Spada, Francesca; Cella, Chiara; Bertani, Emilio; Rubino, Manila; Gibelli, Bianca; Grana, Chiara; Bonomo, Guido; Funicelli, Luigi; Ravizza, Davide; et al.
Graphical abstract: Highlights: Metronomic therapy in NETs can control tumor growth and preserve QoL. Due to its multi-targeted trait this schedule aims disease stability. Radiotherapy and PEG IFN α-2b can be used as metronomic like regimens in NETs. Patients' pharmacokinetics profile is needed to personalize the metronomic approach. Abstract: Metronomic therapy is characterized by the administration of regular low doses of certain drugs with very low toxicity. There have been numerous debates over the empirical approach of this regimen, but fewest side effects are always something to consider in order to improve patients′ quality of life. Neuroendocrine tumors (NETs) are rare malignancies relatively slow-growing; therefore their treatment is often chronic, involving several different therapies for tumor growth control. Knowing that these tumors are highly vascularized, the anti-angiogenic aspect is highly regarded as something to be targeted in all patients harboring NETs. Additionally the metronomic schedule has proved to be effective on an immunological level, rendering this approach as a multi-targeted therapy. Rationalizing that advanced NETs are in many cases a chronic disease, with which patients can live for as long as possible, a systemic therapy with regular low doses and a very low toxicity is in many cases a judicious manner of pursuing stabilization. Metronomic schedule is usually correlated with chemotherapy in oncology, but other therapies, such as radiotherapy and biotherapy can be delivered in a metronomic like manner. This review describes clinical trials and case series involving metronomic therapies alone or in combination in patients with advanced NETs. Nowadays level of evidence about metronomic therapy in NETs is quite low, therefore future prospective clinical studies are needed to validate the metronomic approach in specific clinical settings.